Nasal sprays containing mometasone furoate can be used prophylactically in covid-19 infection and related smell disorders - ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2023)
Objective: We aimed to emphasize the possible beneficial effects of intranasal sprays containing mometasone furoate, especially for preventive treatment or supportive treatment in patients with olfactory disorders due to damage to the olfactory area, or for regular use in healthcare workers with a high risk of close contact. Methods: Preventive and therapeutic scientific studies are continuing around the world for viral spread and viral damage associated with the Coronavirus disease 2019 (COVID-19) pandemic. We investigated the attachment of the COVID-19 virus in the nose and entry into the body with the crystal structure of the spike and Angiotensin-Converting Enzyme 2 (ACE-2) proteins, a molecular docking study. This scientific study is the first in-silico study to investigate the possible antiviral effects of Mometasone furoate molecules on spike protein and to show the antiviral effect of mometasone furoate on COVID-19. Results: We think that nasal sprays containing mometasone furoate can be used prophylactically in patients with COVID-19 infection due to its antiviral effect, and it may be beneficial to use sprays containing mometasone furoate before the symptoms of upper respiratory tract infection begin in patients. Conclusions: The role of these molecules in the treatment of acute smell disorders associated with COVID-19 infection and their antiviral effects on coronavirus should be investigated by conducting extensive scientific studies on the subject.
Keywords: Anosmia; Coronavirus; Mometasone furoate; Prevention; Olfactory disorders